2018
DOI: 10.1186/s13073-018-0514-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection and analysis of methicillin-resistant human-adapted sequence type 398 allows insight into community-associated methicillin-resistant Staphylococcus aureus evolution

Abstract: BackgroundSevere infections with highly virulent community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) are a global problem. However, the molecular events defining the evolution of CA-MRSA are still poorly understood. MRSA of sequence type (ST) 398 is known to frequently infect livestock, while ST398 isolates infecting humans are commonly methicillin-susceptible or represent MRSA originating from livestock-associated (LA)-MRSA.MethodsWe used whole genome sequencing of newly detected CA-MRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 41 publications
(67 reference statements)
6
60
0
Order By: Relevance
“…Phylogenetic analysis showed S23009-2007 had a much closer relationship to the PVL-negative MRSA ST398 isolates from China reported by He et al than to LA-MRSA ST398 isolates from Australia (Figure) ( 7 ). These isolates are grouped within the II-GOI (group of interest) clade from the Price et al study of worldwide MRSA ST398 isolates ( 6 ).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Phylogenetic analysis showed S23009-2007 had a much closer relationship to the PVL-negative MRSA ST398 isolates from China reported by He et al than to LA-MRSA ST398 isolates from Australia (Figure) ( 7 ). These isolates are grouped within the II-GOI (group of interest) clade from the Price et al study of worldwide MRSA ST398 isolates ( 6 ).…”
mentioning
confidence: 71%
“…Phylogenetic tree of MRSA sequence type (ST) 398 isolate S23009-2017, recovered from a man in Australia in 2017, and related MRSA ST398 isolates from around the world ( 2 , 6 , 7 ). The tree was constructed by using single-nucleotide polymorphism differences and is rooted with MRSA ST398 isolates containing a single Panton-Valentine leukocidin locus.…”
mentioning
confidence: 99%
“…From a previous study, 9–29 allelic differences can be considered possibly related, whereas > 30 are considered unrelated ( 11 ). When we compared the strains in our study to MRSA ST398 strain 4_ST398 from a hospital in Shanghai ( 12 ), we found 30–40 allelic differences between each of our 4 strains and the reference strain. There were > 150 allelic differences between the SSI strains in our study and other ST398 strains, including animal- and human-related strains, from other studies ( 7 , 13 , 14 ).…”
Section: The Studymentioning
confidence: 86%
“…Generally, due to the lack of several common virulence factors, the ST398 MRSA in Europe did not cause the frequent invasive diseases in humans 45. However, a recent report indicated that the Chinese LA-MRSA ST398 isolates are far different from those of other continents, because they likely evolved from human-adapted MSSA 46. Recently, a report about the emergence of ST398 in a pig farm in Guangdong, China was published,13 which indicated the transmission of this clone between different continents.…”
Section: Discussionmentioning
confidence: 99%